Endomorphins and ohmefentanyl in the inhibition of immunosuppressant function in rat peritoneal macrophages: An experimental in vitro study - Li, Wei-Yan (Elsevier, 2008)
Background: The potential immunosuppressant effects of opioids might have clinical implications. The effects of endomorphins (EMs) and ohmefentanyl (OMF) on cultured rat peritoneal macrophages remain unclear. Objective: The aim of this study was to investigate the immunosuppressant effects of EMs and OMF on cultured rat peritoneal macrophages in vitro. Methods: Purified rat peritoneal macrophages, from healthy adult male Sprague-Dawley rats, were cultured with EM-1 (EM-1 group), EM-2 (EM-2 group), OMF (OMF group), and saline (saline group). We measured the concentrations of tumor necrosis factor (TNF)-α and interleukin (IL)-β in supernatant when macrophages were cultured with 10(−6) mol/L of EM-1, EM-2, OMF, or saline for 0, 6, 12, and 24 hours (time-effect relationship) or with 10(−10), 10(−9), 10(−8), 10(−7), and 10(−6) mol/L of these substances for 24 hours (concentration-effect relationship). We also determined the phagocytic and bactericidal activities of macrophages using isotope markers when macrophages were cultured with 10(−6) mol/L of EM-1, EM-2, OMF, or saline for 24 hours. Results: Compared with the saline group, TNF-α concentration decreased significantly in the OMF, EM-2, and EM-1 groups at 12 hours (P < 0.05, P < 0.05, and P < 0.01, respectively) and at 24 hours (P < 0.05, P < 0.01, and P < 0.01, respectively). Compared with the saline group, IL-1β concentration decreased signifcantly in the OMF, EM-2, and EM-1 groups at 12 hours (P < 0.05, P < 0.05, and P < 0.01, respectively) and at 24 hours (P < 0.05, P < 0.01, and P < 0.01, respectively). Decreased TNF-α and IL-1β concentrations were observed in the supernatant at 24 hours when cultured with 10(−8), 10(−7), and 10(−6) mol/L in the OMF and EM-2 groups (all, P < 0.05) and in the EM-1 group (all, P < 0.01). Compared with the saline group, macrophage phagocytic activity (all, P < 0.05) and macrophage bactericidal activity (all, P < 0.01) were significantly lower in the 3 experimental groups compared with the saline group. Conclusion: In this in vitro experiment, EM-1, EM-2, and OMF inhibited the immunosuppressant function of cultured rat peritoneal macrophages, including decreasing TNF-α and IL-1β concentrations and phagocytic and bactericidal activities.